Molecular Characterization of Clostridium difficile Isolates in China From 2010 to 2015 - Liu, Xiao-shu; Li, Wen-ge; Zhang, Wen-zhu; Wu, Yuan; Lu, Jin-xing (Frontiers in Microbiology, 2018)
Clostridium difficile infection (CDI) has become a worldwide public health problem causing high mortality and a large disease burden. Molecular typing and analysis is key important for surveillance and infection control of CDI. However, molecular characterization of C. difficile across China is extremely rare. To investigate the multicenter data of C. difficile isolates across China, the toxin profile, molecular types, and epidemiological characteristics of C. difficile were analyzed. A total of 199 C. difficile isolates collected from 2010-2015 were analyzed using multilocus sequence typing (MLST), PCR ribotyping, and toxin genes amplification. There were 35 STs and 27 ribotypes (RTs) identified in this study, in which ST35 (15.58%), ST3 (15.08%), ST37 (12.06%) and RT017 (14.07%), RT001 (12.06%), RT012 (11.56%), are the most prevalent types, respectively. One isolate with ST1 and 8 isolates with ST 11 were identified. We identified a new ST in this study, denoted ST332. The toxin profile tcdA+tcdB+tcdC+tcdR+tcdE+CDT- (65.83%) was the predominant profile. Furthermore, 11 isolates with positive binary toxin genes were discovered. According to the PCR ribotyping, ST1 was confirmed as RT 027, and 6 out of the 8 ST11 strains were confirmed as RT 078. The epidemiological characteristics of C. difficile in China shows geographical differences, and both the toxin profile and molecular types exhibit great diversity across the different areas.